“Crianza de sitotroga cerealella (oliver), en los sustratos de arroz (oryza sativa) carolino, cebada (hordeum vulgare) y maíz amarillo suave (zea mays), para la produccion comercial de trichogramma spp. En San Martín” - López Vásquez, Luis Teófilo (2009)
The experiment was developed at the facilities of the laboratory of breeding useful insects of the UNSM-T, located in the province and region of San Martín Morales. The objective was to: determine the effect of three substrates of power, on the production of eggs and other biological parameters in breeding of Sitotroga cerea / it (Oliver), in laboratory, likewise determine the relation benefit/cost and cost-benefit of the treatments used. The employed design was a completely randomized design with factorial arrangement 3 x 3 with three replications and with a witness by each treatment, making a total of 27 experimental units, used pair this work S. cerea eggs / it. (SENASA-LIMA) 102 g... Substrates (Cebada100kg; Rice ' carolino· 100 kg; Yellow corn suave.1 OOkg). The results show that T6 treatment obtained greater production of eggs postures with 20,23 g during the production cycle of the experimental work. Likewise be pu...